2013
DOI: 10.1292/jvms.13-0041
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Age with Distribution of Periodontitis-Related Bacteria in Japanese Dogs

Abstract: ABSTRACT. We analyzed the distribution of 11 periodontitis-related bacterial species in dental plaque collected from 176 Japanese dogs divided into young (less than 2 years of age), middle-aged (2-7 years of age) and elderly (more than 8 years of age) groups using a polymerase chain reaction method. Clinical examination revealed that no dogs in the young group were affected by periodontitis, whereas the rates for gingivitis and periodontitis were high in the middle-aged and elderly groups. In addition, the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
2
10
0
2
Order By: Relevance
“…5), but this correlation was not signifi cant, probably because of the small number of dogs used in the present study. Our results are in agreement with previous results that periodontal disease is the most widespread oral disease in dogs and incidence increases with advancing age (Kortegaard et al, 2008;Hirai et al, 2013). Further work is also required to confi rm this hypothesis.…”
Section: Correlations Between Vsc Levels and Agesupporting
confidence: 93%
“…5), but this correlation was not signifi cant, probably because of the small number of dogs used in the present study. Our results are in agreement with previous results that periodontal disease is the most widespread oral disease in dogs and incidence increases with advancing age (Kortegaard et al, 2008;Hirai et al, 2013). Further work is also required to confi rm this hypothesis.…”
Section: Correlations Between Vsc Levels and Agesupporting
confidence: 93%
“…In addition, it has been confirmed that age plays a significant part in the progression of periodontitis in both species [1519]. Yamasaki et al [40] demonstrated that the total bacteria count in dogs is positively correlated with animal age.…”
Section: Discussionmentioning
confidence: 99%
“…Oral malodor and periodontal disease are very common in adult humans and dogs. In the previous study (Hirai et al, 2013), we observed a positive correlation between age and periodontal disease in 176 privately owned pet dogs. In the present study, we examined the association between age and oral malodor in 43 laboratory Beagle dogs.…”
Section: Discussionmentioning
confidence: 64%